PERANCANGAN GABUNGAN METODE PROGRESSIVE CAVITY PUMP DAN GAS LIFT DENGAN MENGGUNAKAN NODAL SYSTEM ANALYSIS - Adlirachman, Hafizan
In the old oil wells, fluid can’t be produced at a rate that is economical because the driving force or reservoir pressure has dropped. The decline of the driving force or the reservoir pressure is led to the ability to raise the fluid to the surface will be reduced or even stopped. Therefore, so that the oil can be lifted up to the surface, method of artificial lift is being used. This method is used to help raise the fluid to the surface mechanically, using a pump, or by reducing the weight of the hydrostatic column of fluid through gas injection. In this study will be designed merger between gas lift method with PCP. Gas injection will reduce the density of the fluid in the tubing so as to facilitate the flow to the surface and it can reduce the power requirements of the pump.